2020
DOI: 10.1108/bij-05-2020-0247
|View full text |Cite
|
Sign up to set email alerts
|

Green market segmentation and consumer profiling: a cluster approach to an emerging consumer market

Abstract: PurposeIn the present era of green consumerism, consumers are shifting towards sustainable consumption with the rising demand of green products. Despite consumers' demand of such products, their attitudes towards eco-friendly practices can neither be the same for different consumer groups nor can be treated as they all are equally green. The purpose of this study is to operationalize the green market segmentation based on demographic, psychographic and behavioural characterization in the Indian context of gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 73 publications
4
104
0
4
Order By: Relevance
“…The research by Baker and Wakefield (2012) that investigated how shopping orientation influences the consumers' reaction to the in-store crowding, concluded saying that that task-focused shoppers experience more stress, which has negative consequences on their patronage behavior. The psychographic profiling of green consumers by Jaiswal et al (2020) brought out three segments namely: "keen greens, moderate greens and reluctant greens". While there are many shopping orientation studies with the focus on generational cohorts, they did not go further to explore the inter-generational differences or similarities between the cohorts except in the case of…”
Section: Consumer Decision-making Styles or Shopping Orientationsmentioning
confidence: 99%
“…The research by Baker and Wakefield (2012) that investigated how shopping orientation influences the consumers' reaction to the in-store crowding, concluded saying that that task-focused shoppers experience more stress, which has negative consequences on their patronage behavior. The psychographic profiling of green consumers by Jaiswal et al (2020) brought out three segments namely: "keen greens, moderate greens and reluctant greens". While there are many shopping orientation studies with the focus on generational cohorts, they did not go further to explore the inter-generational differences or similarities between the cohorts except in the case of…”
Section: Consumer Decision-making Styles or Shopping Orientationsmentioning
confidence: 99%
“…Furthermore, consumer psychology clarifies how individuals may be grouped according to their similar attitudes and motivations towards a specific food product. Such segmentation helps in orienting and personalizing communicational and educational initiatives thanks to a better understanding of a segment's interests, attitudes and consumption patterns (Brečić et al, 2017;Jaiswal et al, 2020). Segmentation analysis has been used successfully to identify, profile and select target groups that are most likely to benefit from specific campaigns or messages that promote and enhance the use of sustainable products, providing information on opinions and attitudes of the different groups and consequently facilitating the development of the most appropriate communications strategies (Grasso et al, 2019;Van Loo et al, 2017;Verain et al, 2017;Witzling and Shaw, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this section will start with a discussion of green consumer profiles. Jaiswal et al [24] found that green consumerism is driven by several psychographic variables in an eco-context, such as environmental concern, perceived environmental knowledge, perceived consumer effectiveness, the perception of eco-labels, the perception of eco-brands and environmental advertisements, green purchase intention, and green purchase behavior. Ziaei-Bideh and Namakshenas-Jahromi [25], inter alia, characterized green consumers using sociodemographic variables and found them to be predominantly female, older, less educated, and of a lower income level.…”
Section: Literature Reviewmentioning
confidence: 99%